Embryonic Development and Adult Regeneration of the Adrenal Gland - Kim, Ji-Hoon; Choi, Man Ho (KOREAN ENDOCRINE SOC, 2020)
The adrenal gland plays a pivotal role in an organism's health span by controlling the endocrine system. Decades of research on the adrenal gland have provided multiscale insights into the development and maintenance of this essential organ. A particularly interesting finding is that founder stem/progenitor cells participate in adrenocortical development and enable the adult adrenal cortex to regenerate itself in response to hormonal stress and injury. Since major advances have been made in understanding the dynamics of the developmental process and the remarkable regenerative capacity of the adrenal gland, understanding the mechanisms underlying adrenal development, maintenance, and regeneration will be of interest to basic and clinical researchers. Here, we introduce the developmental processes of the adrenal gland and discuss current knowledge regarding stem/progenitor cells that regulate adrenal cortex remodeling and regeneration. This review will provide insights into the fascinating ongoing research on the development and regeneration of the adrenal cortex.
Keywords: SONIC HEDGEHOG; ADRENOCORTICAL DEVELOPMENT; TARGETED DISRUPTION; NUCLEAR RECEPTOR; STEROID-LEVELS; STEM-CELLS; MOUSE; PROGENITOR; EXPRESSION; DIFFERENTIATION